Russian Cyber-Attacks on Estonia, Georgia, and Ukraine, Including Tactics, Techniques, Procedures, and Effects - Donald L. Buresh (Journal of Advanced Forensic Sciences, 2021)
The purpose of this essay is to compare and contrast the cyber-attacks on Estonia, Georgia, and Ukraine, including tactics, techniques, procedures, and effects. The paper states that none of the models will probably be repeated. The thesis is that cyber-attacks will change as technology changes. In other words, past cyber-attacks operations, particularly in Estonia, Georgia, and Ukraine, are not good predictors of future cyber-attack activity.
Keywords: Cyber-Attack Tactics